(untitled) (Revista Brasileira Multidisciplinar, 2026)
The spinal cord is the main conduit through which motor and sensory information travels between the brain and body, however, spinal cord injury (SCI) affects the conduction of sensory, motor signals through the spinal cord site(s). of the lesion(s) and in the autonomic nervous system. By systematically examining the dermatomes and myotomes, the neurological impairment and level can be determined, which often relates to the individual’s autonomy and functional independence. To analyze the autonomy and functional independence in relation to the neurological level of patients with spinal cord injury. Participation of each individual was in a single session to carry out the assessment consisting of a form, American Spinal Cord Injury Association (ASIA) impairment scale, life satisfaction scale, spinal cord injury independence measure, quality of life and functional autonomy test of adults with spinal cord injury. Eight individuals participated, with a mean age of 48.5±8.8 years, 4 women and 4 men, all of whom were in the chronic phase of spinal cord injury; 2 individuals had incomplete traumatic spinal cord injury and 6 individuals had a diagnosis of incomplete thoracic non-traumatic spinal cord injury, all reported mobility-related disability limitations, which resulted in lower scores in terms of satisfaction with life, functional independence, quality of life and autonomy. The autonomy and functional independence of patients with spinal cord injuries appear to be related to the level of neurological injury.